Quality of Inpatient Services at the Tongas General Hospital, Probolinggo Regency - Nindi Elis; Dety Mulyanti (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to determine the quality of inpatient services at Tongas General Hospital, Probolinggo Regency. The type of research used is qualitative, with the type of case study research. To collect data, researchers used data collection techniques consisting of observation, interviews, and documentation. The results of this study are (1) Physical evidence (tangible) of the existing infrastructure at the Tongas General Hospital in Probolinggo Regency is sufficient and supportive in assisting the service process Inpatients at the hospital but maintenance still needs to be improved. (2) Reliability in the health services of inpatients is good; this dimension is shown by the always-prepared doctors and the skills of the Tongas General Hospital and Probolinggo Regency staff in dealing with inpatients and handling patients following applicable procedures. It must always prioritize professionalism in providing services to patients. (3) The responsiveness of employees or nurses is good because every patient given an action by the nurse is satisfied with the speed of service provided to the patient. (4) Empathy, the patient is satisfied. Because there were no complaints submitted by inpatients regarding this.